The transport of chemical components in homogeneous snowpacks on urumqi glacier no. 1, eastern tianshan mountains, central Asia - You, X.; Li, Z.; Edwards, Peter; Wang, L. (Kexue Chubanshe, 2015)
Chemical records from alpine ice cores provide an invaluable source of paleoclimatic and environmental information. Not only the atmospheric chemical composition but also depositional and post-depositional processes are recorded within snow/firn strata. To interpret the environmental and climatic significance of ice core records, we studied the variability of glacier snowpack chemistry by investigating homogeneous snowpacks from October 2003 to September 2006 on Urumqi Glacier No. 1 in eastern Tianshan Mountains, Central Asia. Principle Component Analysis of ionic species in dry and wet seasons revealed the impact of meltwater in redistributing ions in the snowpacks. The 1st, 2nd and 3rd principle components for dry seasons differ significantly, reflecting complex associations between depositional or/and post-depositional processes. The variability trend of ionic concentrations during the wet seasons was found to fit a Gauss Function with significant parameters. The elution factor revealed that more than half of ions are leached out during the wet seasons. Differences with respect to ion snowpack mobility were found. Of the ions studied SO4 2– was the most mobile and Mg2+ the least mobile. A threshold relationship between air temperatures and the elution process was investigated over the study period. The results indicate that the strong melt /ablation processes and iconic redistribution occur at a threshold air temperature of 0°C. The study found that surface melt on the snowpacks is the main factor causing the alteration of the snowpack chemistry. Rainfall also has an impact on the chemistry but plays a less significant role than the surface melt.